Mokko Lactone Attenuates Doxorubicin-Induced Hepatotoxicity in Rats: Emphasis on Sirt-1/FOXO1/NF-κB Axis - Alaa Sirwi (MDPI AG, 2021)
Doxorubicin (DOX), a common chemotherapeutic agent, suffers serious adverse effects including hepatotoxicity. Mokko lactone (ML) is a guainolide sesquiterpene with promising biological activities. The study aimed to evaluate the protection offered by ML against hepatotoxicity induced by DOX in rats. Our data indicated ML exhibited protective effects as evidenced by ameliorating the rise in serum activities of alanine transaminase, aspartate transaminase and alkaline phosphatase. This was confirmed histologically as ML prevented DOX-induced pathological alteration in liver architecture. Further, ML administration significantly prevented malondialdehyde accumulation, glutathione depletion and superoxide dismutase and catalase exhaustion. Antioxidant action of ML was associated with enhanced expression of the nuclear translocation of NF-E2-related factor 2 (Nrf2) and a lower expression of forkhead box protein O1 (FOXO1). Also, ML showed potent anti-inflammatory activities highlighted by decreased expression of interleukin 6, tumor necrosis factor α and nuclear factor κB (NF-κB). The anti-apoptotic effects of ML were associated with decreased Bax and enhanced Bcl-2 mRNA expression in liver tissues. ML caused a significant up-regulation in the expression of silent information regulator 1 (Sirt-1). Therefore, it can be concluded that ML prevents liver injury caused by DOX. This could partially be due to the ML regulatory activities on Sirt-1/FOXO1/NF-κB axis.